2019
DOI: 10.1111/jar.12571
|View full text |Cite
|
Sign up to set email alerts
|

“Getting into it”: People with intellectual disabilities’ experiences and views of Behavioural Activation and Guided Self‐Help for depression

Abstract: Background No studies have explored the acceptability of Behavioural Activation and Guided Self‐Help interventions for depression with people who have intellectual disabilities. Method Twenty‐five participants were purposively sampled from participants taking part in a trial comparing Behavioural Activation with a Guided Self‐Help intervention. A framework analysis was used to analyse interviews covering participants’ expectations and views of therapy. Results Participants were largely positive about both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Some participants acknowledged they had to put strategies into practice to experience the benefits of therapy, including those attending Currie et al's (2019) mindfulness-based programme, who discussed incorporating the techniques into everyday life. Some of Knight et al's (2019) participants continued to use session booklets to remind them of helpful strategies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some participants acknowledged they had to put strategies into practice to experience the benefits of therapy, including those attending Currie et al's (2019) mindfulness-based programme, who discussed incorporating the techniques into everyday life. Some of Knight et al's (2019) participants continued to use session booklets to remind them of helpful strategies.…”
Section: Resultsmentioning
confidence: 99%
“…I don’t like that I am not a child and I just mean that I don’t need to draw daft pictures of wee people…Just because I have problems I don’t need daft wee pictures with loads of colours to make me feel, I don’t need that. (Knight, et al, 2019, p. 827)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger trial of the present intervention in a similar sample of people with at least subclinical symptoms of reduced well-being is required to more adequately compare both the interventions. A shared finding, however, is that participants with intellectual disabilities in both studies reported a desire for more sessions or an overall longer intervention [36].…”
Section: Discussionmentioning
confidence: 99%
“…A larger trial of the present intervention in a similar sample of people with at least subclinical symptoms of reduced well-being is required to more adequately compare both the interventions. A shared finding, Vereenooghe & Westermann JMIR FORMATIVE RESEARCH XSL • FO RenderX however, is that participants with intellectual disabilities in both studies reported a desire for more sessions or an overall longer intervention [36].…”
Section: Overviewmentioning
confidence: 92%